Critically evaluate merger and acquisition (M&A) activities in Hong Kong - Zhou, Ying (2024)
Hong Kong is a highly developed and mature economy with a well-established framework for mergers and acquisitions (M&A), benefiting from extensive experience in this field (Jin, 1998). Despite the active acquisition activity observed in recent years, there remains a dearth of research on M&A activities specifically in Hong Kong. This thesis aims to address this gap by investigating the predictability of M&A events among companies listed on the Hong Kong Stock Exchange (HKEX) since 2000, with a particular emphasis on identifying key determinants that influence their likelihood of becoming targets for M&A activities. Furthermore, this thesis seeks to evaluate the abnormal returns received by shareholders of target firms during M&A bid announcements. Distinguishing itself from prior studies, this thesis incorporates accounting and macroeconomic variables to identify significant factors at play.